2017
DOI: 10.3389/fphys.2017.00307
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Slc26a1 and Slc26a7 Delays Enamel Mineralization in Mice

Abstract: Amelogenesis features two major developmental stages—secretory and maturation. During maturation stage, hydroxyapatite deposition and matrix turnover require delicate pH regulatory mechanisms mediated by multiple ion transporters. Several members of the Slc26 gene family (Slc26a1, Slc26a3, Slc26a4, Slc26a6, and Slc26a7), which exhibit bicarbonate transport activities, have been suggested by previous studies to be involved in maturation-stage amelogenesis, especially the key process of pH regulation. However, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…Accordingly, we investigated acid-base status in our patients, but all individuals homozygous for SLC26A7 mutations showed normal serum electrolytes and renal function (Supplemental Table 3), with no clinical evidence of achlorhydria. Recent data also support a role for rodent Slc26a7 in dental enamel formation (7); however, our patients did not exhibit abnormal dentition.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Accordingly, we investigated acid-base status in our patients, but all individuals homozygous for SLC26A7 mutations showed normal serum electrolytes and renal function (Supplemental Table 3), with no clinical evidence of achlorhydria. Recent data also support a role for rodent Slc26a7 in dental enamel formation (7); however, our patients did not exhibit abnormal dentition.…”
Section: Resultssupporting
confidence: 77%
“…It also localizes to the basolateral membrane of gastric parietal cells and may either facilitate HCO 3 efflux or function as a Clchannel, regulating gastric acid secretion (14,15,3) in agreement with our localization of Slc26a7 protein to both intracellular and basal membrane compartments in thyroid follicular cells. Additionally, Slc26a7 contributes to maintenance of the pH regulatory network during maturation of murine tooth enamel (7). With documented distal renal tubular acidosis and gastric achlorhydria in Slc26a7-null mice, we found no overt renal acid-base abnormalities in our homozygous SLC26A7-mutant patients in the healthy state, but cannot exclude its role when homeostasis is perturbed, analogous to the renal role of pendrin during systemic metabolic alkalosis (16).…”
Section: Discussionmentioning
confidence: 56%
“…membrane of gastric parietal cells and may either facilitate HCO 3 efflux or function as a Clchannel, regulating gastric acid secretion (14,15,3) in agreement with our localization of Slc26a7 protein to both intracellular and basal membrane compartments in thyroid follicular cells. Additionally, Slc26a7 contributes to maintenance of the pH regulatory network during maturation of murine tooth enamel (7). With documented distal renal tubular acidosis and gastric achlorhydria in Slc26a7-null mice, we found no overt renal acid-base abnormalities in our homozygous SLC26A7-mutant patients in the healthy state, but cannot exclude its role when homeostasis is perturbed, analogous to the renal role of pendrin during systemic metabolic alkalosis (16).…”
Section: Discussionmentioning
confidence: 56%
“…Notably, mutant mouse models have been generated for all SLC26 members, and all reproduced the clinical features of the SLC26 human-related diseases when applicable (Liberman et al, 2002; Forlino et al, 2005; Schweinfest et al, 2006; Touré et al, 2007; Dallos et al, 2008; Dror et al, 2010; El Khouri et al, 2018). In addition, studies of members not so far associated with human diseases (SLC26A7 and A11) revealed their functions in various tissues such as kidney, gastro intestinal tract, enamel, vestibular membrane of the cochlea, and brain (Xu et al, 2009; Rahmati et al, 2013, 2016; Kim et al, 2014; Yin et al, 2017), predicting that further investigations might lead to the identification of novel SLC26 gene mutations associated with pathophysiological conditions in humans (Table 1). Lastly SLC26 function may be critical for cystic fibrosis condition (CF; MIM 219700), a disease which is due to mutations in CFTR, and characterized by general defective electrolyte transport, chronic lung infections and inflammation, respiratory failure, digestive symptoms and male infertility (i.e., congenital bilateral absence of the vas deferens).…”
Section: Slc26 Proteins In Sperm Function and Male Fertilitymentioning
confidence: 99%